AGV of Mechanical Auxiliary Parking Based on Self Driving. Issue 3 (April 2021) - Sun, Haotian; Zhang, Wenbo; Xie, Anbo
Abstract: In order to solve the problem of parking difficulties in urban residential areas, a small auxiliary parking device is proposed. Starting from solving the social pain points such as unreasonable parking space planning, residents' random parking, and reducing parking difficulty, it achieves the effect of assisting parking space planning and reducing parking difficulty. The device mainly provides power through the motor, and drives the drum to realize binary control by controlling the steering wheel of the vehicle owner, that is, controlling the switching of the whole movement, and the switching of the front back and left right of the control device. By pressing the spring switch on the wheel, the front control motor drives the gear clutch device to complete the bidirectional switching from left and right movement to back and forth movement. Through the shear fork supporting mechanism and separate self-locking slide rail, the car is lifted and the parking device is driven away.